Emodin enhances cisplatin-induced cytotoxicity in human bladder cancer cells through ROS elevation and MRP1 downregulation. Issue 1 (December 2016) - Li, Xinxing; Wang, Haolu; Wang, Juan; Chen, Yuying; Yin, Xiaobin; Shi, Guiying; Li, Hui; Hu, Zhiqian; Liang, Xiaowen
Abstract Background Chemoresistance is one of the most leading causes for tumor progression and recurrence of bladder cancer. Reactive oxygen species (ROS) plays a key role in the chemosensitivity of cancer cells. In the present study, emodin (1, 3, 8-trihydroxy-6-methylanthraquinone) was applied as a ROS generator in combination with cisplatin in T24 and J82 human bladder cancer cells. Methods Cell viability and apoptosis rate of different treatment groups were detected by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and flow cytometry (FCM). The expression of transporters was measured at both the transcription and translation levels using PCR and western blotting. In vitro findings were confirmed by in vivo experiments using tumor-bearing mice. The expression of multidrug resistance-associated protein 1 (MRP1) in tumour tissue was measured using immunohistochemistry and side effects of the emodin/cisplatin co-treatment were investigated by histological examination. Results Emodin increased the cellular ROS level and effectively enhanced the cisplatin-induced cytotoxicity of T24 and J82 human bladder cancer cells through decreasing glutathione-cisplatin (GSH-cisplatin) conjugates. It blocked the chemoresistance of T24 and J82 cells to cisplatin through suppressing the expression of MRP1. This effect was specific in T24 and J82 cells but not in HCV-29 normal bladder epithelial cells. Consistent with in vitro experiments, emodin/cisplatin co-treatment increased the cell apoptosis and repressed the MRP1 expression in xenograft tumors, and without obvious systemic toxicity. Conclusions This study revealed that emodin could increase the cisplatin-induced cytotoxicity against T24 and J82 cells via elevating the cellular ROS level and downregulating MRP1 expression. We suggest that emodin could serve as an effective adjuvant agent for the cisplatin-based chemotherapy of bladder cancer.